(untitled) (Journal of the College of Basic Education, 2025)
Imam Ali ibn Abi Talib (peace be upon him) is regarded as one of the most prominent Islamic figures, in whom political thought merged with eloquent wisdom and just leadership. His political discourse constitutes a fundamental part of Islamic heritage, not only for its rich content but also for the profound impact it left on intellectual, cultural, and literary thought across generations. This discourse is distinguished by its humanistic and reformative nature, calling for social justice, accountability of rulers, rejection of oppression, and prioritization of public interest over personal desires. Amid the intellectual transformations witnessed in the modern Arab world, and with the emergence of reformist and revolutionary literary movements, the discourse of Imam Ali has re-emerged—not merely as a religious legacy, but as an inspiring source for modern literary visions seeking justice, freedom, and dignity in the face of political and social tyranny. This study explores the question of how Imam Ali’s political discourse contributed to shaping the intellectual and literary awareness of contemporary Arab writers, and examines its influence on the structure of modern poetic and prose texts. The research adopts analytical, historical, and comparative methodologies, drawing on classical sources such as Nahj al-Balagha and modern critical studies. The subject is characterized by its rich content and profound symbolism, making it a worthy focus of contemporary literary scholarship